Geography human geography : student guide - Dunn, Cameron (Hodder Education Group, 2021)
Reinforce understanding throughout the course with clear topic summaries and sample questions and answers to help students target higher grades. Written by experienced subject expert Cameron Dunn, this Student Guide is divided into two key sections - content guidance, and sample questions and answers. Content guidance will: - Develop understanding of key concepts and terminology in key human geography topics globalisation, regenerating places, diverse places, superpowers, health, human rights and intervention, and migration, identity and sovereignty. - Consolidate knowledge with 'knowledge check questions' at the end of each topic and answers in the back of the book. Sample questions and answers will: - Build understanding of the different question types, so that students can approach each question with confidence. - Enable students to target top grades in their exam paper with sample answers and commentary explaining exactly why marks have been awarded.